PENGARUH STATUS EKONOMI ORANG TUA TERHADAP PRESTASI BELAJAR SISWA-SISWI DI SMP SATU ATAP PATUMBAK - Yana, Yanti (Fakultas Agama Islam, 2020)
The influence of the economic status of parents is a very big influence on the child's process because the family is the first social institution in human life. And in reality, in real life, many parents with high socioeconomic status do not experience any difficulty in fulfilling their children's educational needs because they have money, so such as school fees, school supplies such as laptops, motorbikes, etc., can be fulfilled, because they have money and with money they can make everything happen. However, it is different for parents whose economy is low, so that in fulfilling their children's educational needs and supplies it becomes a significant problem, by not meeting the educational needs of a child and being supported by some parents. With this research, building only to see the effect of the socioeconomic status of parents on student achievement. Where the socioeconomic status of the parents is a picture of the condition of the parents in terms of socioeconomic terms, that picture is material, vital, and spiritual. Meanwhile, student learning achievement is the result of activities expressed in the form of symbols, letters, sentences that can reflect what has been achieved by each child in a certain period of value. This study aims to analyze the socioeconomic status of parents on learning achievement in Islamic religious education. The results showed that the socioeconomic status of parents had a significant effect on learning achievement of Islamic religious education. The socioeconomic status of parents has a significant effect on student consumer behavior. Likewise, economic learning achievement has a significant effect on student consumption behavior. This type of research is descriptive qualitative research which tends to use analysis. Based on the research results, the influence of parents 'socio-economic status on students' learning achievement of Islamic religious education is still quite good, according to the author, because of their very interest in Islamic religious education, this is because the application of loving religion is not started early on.